Analisis Efektifitas Rigging Karakter Animasi â€œTeater Merah Putihâ€ Menggunakan Dua Metode - ilham albana; Hellik Hermawan; Muhammad Abdul Kafi Thosien (Jurnal Komputer Terapan, 2022)
Many animation industry players, especially animated films, are oriented toward the television industry. Therefore, the term "catch up" requires animation film industry players to produce animated films quickly. Industry players are certainly looking for various ways to speed up the process of making animated films, but they still want good and consistent quality. Rigging is an important part of the animated film process, as it is difficult for animators to animate without rigs in animated characters. Rigging isn't just about adding rigs to characters. In the process of making rigs, it is not just making rigs, but the animators can easily animate 3D characters to speed up the animation process. This will speed up your production process by speeding up the animation process because of the convenient controls. Researchers tested two commonly used rigging methods for 3D characters. From this test, it can be shown which rigging method is more effective and faster, to be used on animated characters so that it is faster in the production stage.